Fostering Corporate Social Responsibility and Sustainable Development: A critical analysis and perspective on the organizational strategies implemented by corporations - Ayande, Alpha; Sabourin, Vincent; Cuevas Moreno, Ricardo (Advances in Social Sciences Research Journal, 2015)
Purpose – The research focuses on the analysis of hundreds of articles on the promotion of ethical and moral values for corporate social responsibility (CSR) and sustainable development. This theoretical framework analyzes the CSR, ethical values, and sustainable development in terms of relevance and efficiency, and asks why these points are relevant, and what they have in common in terms of obstacles and drivers for social performance. This paper also tries to identify who will be the winners of all these strategies implemented on a local and global level. Several lines of thought emerge in the context of this theoretical analysis of academic texts and reports. Indeed, factors related to education and vocational training, communication, the sphere of influence of the company, culture, governance and performance evaluation of the CSR actions are paramount. Given the multiplicity of actors, this research has not identified a specific category of actors as being the only winner of the promotion of sustainable development. Our theoretical analysis advocates a new business practice that takes into greater account the ecological, economic and social challenges. The research also proposes the setting up of policies aimed at drastically reducing the economic and social inequalities in order to promote certain ethical and moral values of social responsibility and sustainable development of enterprises and countries. Each region is specific with regards to its sociological context, and in harmonizing global and local challenges. The discourses are still different, even when the conceptual framework of CSR is understood. What is the significance of responsibility? Given the aforesaid, what is conventional here, could be unconventional somewhere else. This would dictate the lack of a coherent approach in the creation of a global village. We emphasize that education plays a crucial role in understanding the practices of CSR and sustainable development management. From this perspective, it is necessary to nest or coordinate the conceptual and operational strategies of the company, so that intentions can be translated into concrete and consistent practices.